Response to rituximab in children and adults with immune thrombocytopenia (ITP) - Emily M. Harris; Kirsty Hillier; Hanny Al‐Samkari; Laura Berbert; Rachael F. Grace (Research and Practice in Thrombosis and Haemostasis, 2021)
Abstract Background Rituximab is a monoclonal anti‐CD20 antibody used as a second‐line treatment for immune thrombocytopenia (ITP). As additional treatments for ITP emerge, identifying the most appropriate patients and optimal timing for rituximab are important but challenging without established predictors of response to therapy. Objectives The purpose of this study was to describe demographic, clinical, and laboratory characteristics of pediatric and adult patients with ITP to identify differences in evaluation before rituximab administration and correlates of platelet response. Methods This is a retrospective cohort study describing the characteristics of patients with ITP treated with rituximab from 2010 to 2020 at two academic tertiary care centers. Results A total of 64 patients met criteria for inclusion. Complete rituximab response (56%) was not significantly different between children (58%, n = 24) and adults (55%, n = 40). Response rate was similar in those with primary versus secondary ITP (53% vs 62%). Among patients treated with rituximab, Evans Syndrome was more common in children than adults (42% vs 18%). Immunologic labs assessed before rituximab varied by age and were more commonly evaluated in children (lymphocyte subsets 88% vs 22%). Immunologic markers, including antinuclear antibody, direct antiglobulin testing, immunoglobulin levels, and lymphocyte subsets, did not predict response to rituximab in pediatric or adult patients with ITP. Conclusions Pre‐rituximab immunologic evaluation varied significantly between adults and children, which could represent institution‐specific practice patterns or a more general practice difference. If the latter, underlying immunodeficiency in adults with ITP may be underrecognized. Standardized guidance for pre‐rituximab immunologic evaluation is needed.